Reducing Mortality in the Perioperative Period - Landoni, Giovanni; Ruggeri, Laura; Zangrillo, Alberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book describes the techniques, strategies, and drugs that have been demonstrated by well-documented randomized trials to influence survival in the perioperative setting. It takes into consideration all types of adult surgery and will be relevant to the evaluation of any patient undergoing an operative procedure. Each chapter focuses on a specific procedure, device, or drug. The scope is accordingly wide, with coverage of topics as diverse as chlorhexidine oral rinse, clonidine therapy, insulin infusion, intra-aortic balloon pump support, leukodepletion, neuraxial anesthesia, and noninvasive respiratory support, to name but a few. In addition, the risks and benefits of using a web-based consensus process (as in this book) to identify effective means of reducing perioperative mortality are discussed. The clear text is supported by "how to do" sections and "key points" boxes that provide easily accessible practical information. Written by acknowledged international experts, Reducing Mortality in the Perioperative Period will be of interest for a wide variety of specialists, including surgeons, cardiologists, anesthesiologists, and intensivists.
Foreword -- Preface -- 1 The risks and benefits of the consensus process -- 2 The process of consensus building -- 3 Noninvasive Ventilation to reduce perioperative mortality -- 4 Role of inhalational anesthetic agents in reducing perioperative mortality -- 5 Can Neuraxial Anesthesia Reduce Perioperative Mortality -- 6 Role of perioperative hemodynamic optimization in reducing perioperative mortality -- 7 Levosimendan to reduce perioperative mortality -- 8 Could Clonidine Contribute to a Reduction in Perioperative Mortality -- 9 Perioperative gb(B-blocker therapy to improve survival -- 10 Perioperative supplemental oxygen to reduce perioperative mortality -- 11 Leukocyte depletion of transfused blood to reduce perioperative mortality -- 12 Chlorhexidine Oral Rinse to reduce perioperative mortality -- 13 Reducing perioperative mortality with Intra Aortic Balloon Counterpulsation (IABP) -- 14 Selective Decontamination of the Digestive Tract -- 15 Role of insulin in reducing mortality in the perioperative period -- 16 Aprotinin: pharmacological benefits and safety concerns -- 17 Consensus Conference on perioperative mortality: an update -- Subject Index.s
Keywords: Medicine; Toxicology; Anesthesiology; Critical care medicine; Cardiology; Surgery; Medicine & Public Health; Surgery; Intensive / Critical Care Medicine; Anesthesiology; Cardiology; Pharmacology/Toxicology.